CARDIOVASCULAR COMPLICATIONS AND ENDOTHELIAL DYSFUNCTION IN PRIMARY VASCULITIS - L A Strizhakov; S V Moiseev; E N Semenkova; E I Kuznetsova (Терапевтический архив, 2012)
Russian and foreign data on development of atherosclerosis in patients with primary vasculitis are analysed. The discussion covers the role of risk factors, features of pathogenesis of atherosclerosis in primary vasculitis, diagnostic and therapeutic methods in this disease.